A university without ruins: Some reflections on possibilities and particularities of an African university - Waghid, Y. (South African Journal of Higher Education, 2017)
Ron Barnett’s (2016) Understanding the university announces that 'the university is a task without end … [and] since the university is always on the move, always moving in its spaces – economic, social, political, cultural, institutional and so on – its possibilities will always be moving on' (Barnett 2016, 9). I concur with Barnett’s cogent analytical take on the contemporary university, and draws on his three-pronged analysis, namely that a university is an institution and an idea; it is an institution in the present with future possibilities; and that it embodies a set of particulars and universals. The particulars and universals want to offer, firstly, a defence of a university as a democratic institution. Secondly, in line with Jacques Derrida’s (2004) novel thoughts on a contemporary university, I make a case for a university as a responsible institution-in-becoming within an African context, thereby bringing into contestation the notion that a university can ever be ‘in ruins’.